Classroom Management for Tertiary Level Students to Minimize Their Anxiety in English Language Learning - Dewi Rizka Nur Alfiana; Ima Mutholliatil Badriyah (Program Studi Pendidikan Agama Islam, Universitas Muhammadiyah Bandung, 2024)
This study was focused on investigating students' anxiety level when learning English especially when implementing grammar into writing. This study also aims to analyze the factors that influence anxiety in students when implementing English grammar, especially tenses, into their writing and how they manage their anxiety. The method used in this research is mixed method with Explanatory Sequential Mixed method approach which requires two phases of data collection, namely quantitative data and qualitative data. The instrument used in this research is a 4-Point Likert Scale questionnaire which contains 33 statement items divided into 3 subscales (Grammar Learning, Learners' Beliefs, and Grammar Learning Experience) and interview. The subject of this study was 50 students majoring in English Education. The result showed that students' grammar anxiety level on grammar learning subscale indicated low (64%), on learners' beliefs subscale indicated high (82.13%), and on grammar learning experience indicated high (77%). The influencing factors include internal factors such as fear of negative evaluation, fear of mistakes, lack of knowledge about grammar, lack of preparation. The external factors are less fun class situation, students' previous study about grammar, classmates. The strategies that the students used to manage their anxiety was by incidental and intentional grammar learning and using AI grammar checker such as Grammarly.